Effect of garlic extract on growth performances and hematological parameters of broilers - Khan, Md Shafiqul Islam; Prodhan, Md Shoaib; Islam, Md Shahidul; Hasan, Md Nazmul; Islam, Md Shajadul (Asian Journal of Medical and Biological Research, 2017)
This experiment was conducted to evaluate the efficacy of garlic (Allium sativum) extracts supplementation in drinking water as a growth promoter of broiler chicken. A total of 60 one-day-old male Lohman meat broiler chicks were distributed over two groups of 30 chicks with three replicates of 10 birds. Group B was supplemented with garlic extract from water and Group A kept as a control. Weekly observations were recorded for live body weight gain up to 4th weeks and hematological tests were performed at 30th days. Live weight and weight gain of the treatment group were significantly (p<0.05) higher than that of the control group. Significant (p<0.05) higher values also observed in terms of weight of heart, liver, spleen, and pancreas for the treatment group. The value of TEC and PVC of treatment group showed significant (p<0.05) differences. The results suggest that better growth performance could be achieved in broilers with feed supplemented with garlic extract. Asian J. Med. Biol. Res. September 2017, 3(3): 317-322